First report of epidemic dengue fever and malaria co-infections among internally displaced persons in humanitarian camps of North Darfur, Sudan - Ahmed, Ayman; Eldigail, Mawahib; Elduma, Adel; Breima, Tagwa; Dietrich, Isabelle; Ali, Yousif; Weaver, Scott C. (International journal of infectious diseases, 2021)
This study aimed to investigate an outbreak of a non-malaria, undifferentiated febrile illness, among internally displaced persons (IDPs) living in humanitarian camps in North Darfur, Sudan, in 2019. An investigation team was deployed to North Darfur to identify suspected cases and collect blood samples, and clinical and demographical data. Blood samples were examined microscopically for Plasmodium spp and tested for dengue (DENV) and yellow fever viruses by reverse transcriptase-quantitative polymerase chain reaction. Between September 7 and December 18, 2019, we clinically identified 18 (24%), 41 (54%), and 17 (22%) cases of dengue fever, dengue with warning signs, and severe dengue, respectively. Blood samples were collected from 22% of patients, and 47% of these tested positive for DENV-1 RNA. We confirmed 32 malaria cases with 5 co-infections with DENV. This outbreak of dengue was the first among IDPs in the humanitarian camps. Our findings indicate that dengue has become endemic or that there has been a new introduction. Further epidemiological, entomological, and phylogenetic studies are needed to understand disease transmission in the area. An early warning and response system and an effective health policy are crucial for preventing and controlling arboviruses in Sudan.